AN EMPIRICAL EVIDENCE OF HOW SUSTAINABILITY DISCLOSURE AFFECTS FIRM VALUE THROUGH SYSTEMATIC RISK - Steffi Nontji; Fransiskus Eduardus Daromes; Kunradus Kampo (Magister Akuntansi, Universitas Atma Jaya Makassar, 2022)
The purpose of this study is to investigate the effect of sustainability report disclosure on firm value which is tested both directly and through the role of systematic risk. The research model is built on the arguments of stakeholder theory and agency theory to explain the relationship between research variables. The population used in this study are non-financial companies listed on the Indonesia Stock Exchange (IDX) with a research period of 2017-2019. This research uses purposive sampling method. The number of samples obtained as many as 28 companies. Path analysis was used to analyze the data and the mediation hypothesis was tested using the Sobel test. The results of this study indicate that the sustainability report has a negative and significant effect on systematic risk, systematic risk has a negative and significant effect on firm value, and the sustainability report has a positive and insignificant effect on firm value. The results of the Sobel test show that systematic risk mediates the effect of sustainability reporting on firm value.